2008
DOI: 10.1124/jpet.108.139337
|View full text |Cite
|
Sign up to set email alerts
|

MDMA (3,4-Methylenedioxymethamphetamine)-Mediated Distortion of Somatosensory Signal Transmission and Neurotransmitter Efflux in the Ventral Posterior Medial Thalamus

Abstract: MDMA (3,4-methylenedioxymethamphetamine, Ecstasy) is reported to enhance tactile sensory perception, an effect that is believed to contribute to its popularity as a recreational drug. To date, no literature exists that addresses the neurophysiological mechanisms underlying the effects of MDMA on somatosensation. However, MDMA interactions with the serotonin transporter protein (SERT) are well known. The rat trigeminal somatosensory system has been studied extensively and receives serotonergic afferents from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 33 publications
3
24
0
Order By: Relevance
“…From this comparison, the authors concluded that MDMA doses in rats must be 4-fold higher than human doses to achieve similar peak plasma MDMA concentrations and that MDMA pharmacokinetics are linear in rats. Because there are published findings contradicting both of these conclusions (Chu et al, 1996;Delaforge et al, 1999;Starr et al, 2008;, we sought to investigate these issues in more detail.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…From this comparison, the authors concluded that MDMA doses in rats must be 4-fold higher than human doses to achieve similar peak plasma MDMA concentrations and that MDMA pharmacokinetics are linear in rats. Because there are published findings contradicting both of these conclusions (Chu et al, 1996;Delaforge et al, 1999;Starr et al, 2008;, we sought to investigate these issues in more detail.…”
Section: Discussionmentioning
confidence: 99%
“…Starr et al (2008) reported plasma MDMA C max of 300 ng/ml in male LongEvans rats given i.p. injections of 3 mg/kg MDMA, and this concentration is in line with the findings reported here and elsewhere ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In human subjects the popular recreational drug "ecstasy" (MDMA) produces powerful, yet poorly understood, effects on somatosensation (for review, see Starr et al, 2008). We reported previously that single-dose (naive subject) systemic administration of MDMA suppresses the transmission of sensory signals through the rat somatosensory thalamus (Starr et al, 2008).…”
Section: Introductionmentioning
confidence: 99%